Hubungan Pola Makan Modern dengan Terjadinya Impaksi Gigi Molar Ketiga - Ekawati, Mida; Heriyanto, Yonan; Restuning, Sekar; Widyastuti, Tri (Jurnal Terapi Gigi dan Mulut, 2025)
The prevalence of third molar tooth impaction ranges from 20% – 30% in many populations in the world. The report of Berkah Pandeglang Hospital in 2023 shows that of the 1,706 patients who underwent examinations, men were more likely to experience a third molar impact (62.2%) than women (37.8%). Preliminary surveys showed that 6 out of 10 patients examined had a third molar tooth impact, with a diet dominated by fast food, sweets, and soft drinks. This study aimed to determine the relationship between modern diet and the occurrence of the third molar tooth impaction at Berkah Pandeglang Hospital, Banten in 2024. The type of research used was quantitative analysis with a case control design. A sample of 43 respondents with two groups. The sampling technique uses accidental sampling. The research instrument used a questionnaire. Data analysis uses univariate and bivariate. The results of the study showed that as many as 50% experienced the third molar tooth impaction, 46.5% stated that they often followed a modern diet, 27.9% admitted occasionally and 25.6% stated that it was rare. There was a relationship between modern diet and the occurrence of the third molar tooth impaction at Berkah Pandeglang Hospital Banten in 2024, (p=0.000). It is hoped that the public will be more aware of the importance of a healthy and balanced diet, by reducing the habit of following a modern diet such as the consumption of processed foods and high in sugar and is encouraged to regularly check their teeth to prevent impact.